Recent Seismic Sequences and Activation of Normal Fault Systems in the Mugello Basin and Surrounding Areas (Northern Apennines, Italy) - Saccorotti, Gilberto; Bruni, Rebecca; Bonini, Marco; Corti, Giacomo; Keir, Derek; Sani, Federico (Frontiers in Earth Science, 2022)
The Mugello Basin (North-Eastern Tuscany) is an intermontane basin of the Northern Apennines (Italy) with a well-documented record of seismicity; the two major historical earthquakes occurred in 1542 (Mw = 6.0) and in 1919 (Mw = 6.4). In this study, we integrate different seismic catalogs spanning the 2005–2019 time interval, and complement these data with phase arrival times from a temporary network that specifically operated in the area throughout the 2019–2021 time interval. The subsequent relocation of this data set with a double-difference algorithm allows for accurate analyses of the most relevant seismic sequences which affected the study area in 2008, 2009, 2015–2017, and 2019. These sequences are associated with the activation of adjacent segments of larger NW-striking fault systems, one of which bounds the NE margin of the Mugello Basin (Ronta Fault System). For each seismic sequence, best-fit fault surfaces are derived from orthonormal regression of relocated hypocenters, yielding consistent results with that derived from fault plane solutions. The four sequences mark a significant increase in the seismicity rate with respect to what was recorded in the previous decades. This suggests that, following the 2008 renewal of seismicity, static or dynamic stress changes, or both depending on the case, played a role in advancing the time of failure of the fault segments activated subsequently.